Development of Differentiated Instruction-Based LKS to Improve Grade VIII Students' Understanding of SPLDV Material at SMPN 2 Enrekang - Burhan Burhan; Putriani Putriani; Rustiani Rustiani (Universitas Muhammadiyah Enrekang, 2024)
This study aims to develop Student Worksheets (LKS) based on Differentiated Instruction (DI) to improve the understanding of eighth grade students on the material of Two-Variable Linear Equation Systems (SPLDV) at SMPN 2 Enrekang. The method used is research and development (R&D) with the ADDIE model which includes five steps: needs analysis, product design and development, implementation, evaluation, and data analysis. The results of the study indicate that the application of DI-based LKS can improve students' understanding of SPLDV material, as evidenced by a significant increase in pre-test and post-test results. DI-based LKS provides questions with a level of difficulty that is adjusted to the student's abilities, so that each student can learn according to their abilities. Thus, this study suggests the use of DI-based LKS for other mathematics materials as an effort to improve the quality of learning and student learning outcomes.